Comparative morphology of changeable skin papillae in octopus and cuttlefish. (3rd December 2013) - Allen, Justine J.; Bell, George R. R.; Kuzirian, Alan M.; Velankar, Sachin S.; Hanlon, Roger T.
ABSTRACT A major component of cephalopod adaptive camouflage behavior has rarely been studied: their ability to change the three‐dimensionality of their skin by morphing their malleable dermal papillae. Recent work has established that simple, conical papillae in cuttlefish (Sepia officinalis) function as muscular hydrostats; that is, the muscles that extend a papilla also provide its structural support. We used brightfield and scanning electron microscopy to investigate and compare the functional morphology of nine types of papillae of different shapes, sizes and complexity in six species: S. officinalis small dorsal papillae, Octopus vulgaris small dorsal and ventral eye papillae, Macrotritopus defilippi dorsal eye papillae, Abdopus aculeatus major mantle papillae, O. bimaculoides arm, minor mantle, and dorsal eye papillae, and S. apama face ridge papillae. Most papillae have two sets of muscles responsible for extension: circular dermal erector muscles arranged in a concentric pattern to lift the papilla away from the body surface and horizontal dermal erector muscles to pull the papilla's perimeter toward its core and determine shape. A third set of muscles, retractors, appears to be responsible for pulling a papilla's apex down toward the body surface while stretching out its base. Connective tissue infiltrated with mucopolysaccharides assists with structural support. S. apama face ridge papillae are different: the contraction of erector muscles perpendicular to the ridge causes overlying tissues to buckle. In this case, mucopolysaccharide‐rich connective tissue provides structural support. These six species possess changeable papillae that are diverse in size and shape, yet with one exception they share somewhat similar functional morphologies. Future research on papilla morphology, biomechanics and neural control in the many unexamined species of octopus and cuttlefish may uncover new principles of actuation in soft, flexible tissue. J. Morphol. 275:371–390, 2014. © 2013 Wiley Periodicals, Inc.